2023
DOI: 10.1177/11795549231178171
|View full text |Cite
|
Sign up to set email alerts
|

Survival Outcome and Prognostic Factors Among Patients With Hepatocellular Carcinoma: A Hospital-Based Study

Abstract: Background: Hepatocellular carcinoma (HCC) is a leading cancer with very high incidence and mortality and low survival rate in Vietnam and worldwide. This study aimed to investigate the survival outcome and its prognostic factors among HCC patients. Methods: This is a retrospective descriptive study on patients newly diagnosed with HCC at Hanoi Oncology Hospital, Vietnam from January 2018 to December 2020. Overall survival (OS) was calculated by the Kaplan-Meier method. Log-rank test and Cox regression were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…As well, Le et al [11] who reported that hepatocellular carcinoma patients living in the rural area more likely died at home than those living in the urban area, [P = 0.007]. In addition, Bhattarai et al [12] reported that a total of 338 [56.4 %] of patients with liver cirrhosis were from rural areas.…”
Section: Discussionmentioning
confidence: 96%
“…As well, Le et al [11] who reported that hepatocellular carcinoma patients living in the rural area more likely died at home than those living in the urban area, [P = 0.007]. In addition, Bhattarai et al [12] reported that a total of 338 [56.4 %] of patients with liver cirrhosis were from rural areas.…”
Section: Discussionmentioning
confidence: 96%
“…Cirrhosis is associated with liver decompensation, portal hypertension, and impaired liver function, all of which contribute to poorer outcomes in HCC patients. Nevertheless, the overall health status of patients with HCC, including performance status (e.g., Eastern Cooperative Oncology Group performance status), influences treatment eligibility and prognosis [10,11]. Regarding the influence of etiology on treatment outcome, current real-world studies have not demonstrated a significant difference in overall survival for the use of atezolizumab/bevacizumab in patients with viral-associated HCC compared with alcohol-associated HCC and nonalcoholic fatty liver disease-associated HCC [12].…”
Section: Risk-factors and Diagnostic Algorithm Of Hccmentioning
confidence: 99%
“…Currently, the global five-year survival rate of metastatic HCC is <20% ( 3 ). Great progress has been made in the diagnosis and treatment of HCC, but the mortality rate remains unsatisfactory ( 3 , 4 ). According to the stage of the tumor and the condition of the patient, there are various treatment options for HCC.…”
Section: Introductionmentioning
confidence: 99%